Analisis Beban Kerja dan Burnout Bidan terhadap Implementasi Keselamatan Maternal-Neonatal di Kota Balikpapan - Yuniar, Dewi (Jurnal Dunia Kesmas, 2025)
This study aims to analyze the influence of workload and burnout on the implementation of maternal–neonatal safety in primary healthcare facilities in Balikpapan City. The research background arises from the increasing complexity of midwifery services and growing administrative demands, which may trigger emotional exhaustion and decrease compliance with patient safety standards. A quantitative approach with a cross-sectional design was employed. The population consisted of 320 active midwives, and 175 respondents were selected using proportional stratified random sampling. Data were collected using standardized questionnaires measuring workload, burnout, and maternal–neonatal safety implementation. Data analysis was conducted using chi-square tests and multiple linear regression.The findings revealed that workload (β = –0.274; p < 0.01) and burnout (β = –0.321; p < 0.01) had significant negative effects on the implementation of maternal–neonatal safety. Midwives with higher workload and burnout levels tended to demonstrate lower adherence to standard operating procedures (SOPs), incident reporting, and complication prevention practices. Conversely, longer work experience was associated with better safety implementation, although the relationship was not statistically significant.These results support the Job Demands–Resources (JD-R) model, emphasizing that excessive job demands without sufficient organizational support can lead to psychological exhaustion, ultimately reducing performance and workplace safety. This study highlights the importance of effective workload management, burnout prevention, and the strengthening of a safety culture through reflective supervision and continuous training to improve the quality of maternal–neonatal services in primary healthcare settings.